A Practical Guide to Hair Graft Placement Using the Sharp Implanter Method - Park JH; Ho YH; Manonukul K (Clinical, Cosmetic and Investigational Dermatology, 2023)
Jae Hyun Park,1 Yeh Hong Ho,2 Kotchamol Manonukul3 1Dana Plastic Surgery Clinic, Seoul, Korea; 2Dana Taipei Hair Transplantation Clinic, Taipei City, 106, Taiwan, People’s Republic of China; 3V Design Hair by Dana International, Vibhavadi Hospital, Bangkok, 10900, ThailandCorrespondence: Jae Hyun Park, Dana Plastic Surgery Clinic, 10F Samju Building, Gangnamdaero 606, Gangnamgu, Seoul, Korea, Tel +82-2-512-0922, Fax +82-2-512-0942, Email jay8384@naver.comPurpose: Hair transplantation using the sharp implanter method is increasing in popularity. However, there has been little discussion pertaining to surgical know-how or specific techniques that increase efficiency and precision. We describe surgical techniques that enable dense packing in a swift and efficient fashion with the sharp implanter method using photos and videos.Patients and Methods: Grafts were placed using the sharp implanter method while adhering to several important principles. Eleven principles regarding the following aspects of hair transplant surgery were explained: gripping the implanter, graft placing technique that minimizes graft popping and tissue trauma when using the implanter, efficient team surgery system with assistant staff, direction and sequence of graft insertion, effective regimen for using epinephrine to control bleeding, selection of appropriately sized implanter tip, selection and usage of wide and narrow channel implanter tips, importance and methods of depth control, and staff training.Results: High graft survival and dense and natural hair density can be obtained with the sharp implanter method when performed in compliance with the principles described here.Conclusion: Appropriate use of the sharp implanter technique allows efficient and rapid graft insertion and achieves natural outcomes.Keywords: hair follicle, hair transplant, implanter, sharp implanter, alopecia